Islamic Business Ethics of Small Industries in Blitar District - Nana Alfiana (Cahaya Abadi Publisher, 2023)
Islam was revealed as a code of moral and ethical behavior for life. The sources of values ​​and ethics in all aspects of human life as a whole, including in the business world, are the Koran and Hadith. The Al-Quran provides instructions for things to be harmonious, mutually pleased, and there are no elements of exploitation. The type of research used in this research is qualitative research. The purpose of this research is to find out the analysis of the application of sales ethics in the Gadung cracker industry according to business ethics from an Islamic perspective and to find out the analysis of the application of transaction ethics in the Gadung cracker industry according to business ethics from an Islamic perspective. The results of the research state that sales ethics. In reality, all producers cannot implement all the principles of buying and selling ethics. Mrs. Nanik's home industry applies the principle of honesty or truth as a priority. From the results of observations related to the application of transaction ethics carried out in Mrs. Nanik's industry, she has implemented transaction ethics in accordance with sharia transaction principles. Even though the implementation is appropriate, the basis for the transactions carried out is the benefit. When transactions use the principle of benefit, which is the basis of this transaction principle, it covers all the principles of sharia transactions, so that Mrs. Nanik's home industry has carried out sharia transactions in accordance with Islamic law. From the results of observations related to the application of transaction ethics carried out in Mrs. Nanik's industry, she has implemented transaction ethics in accordance with sharia transaction principles. Even though the implementation is appropriate, the basis for the transactions carried out is the benefit. When transactions use the principle of benefit, which is the basis of this transaction principle, it covers all the principles of sharia transactions, so that Mrs. Nanik's home industry has carried out sharia transactions in accordance with Islamic law. From the results of observations related to the application of transaction ethics carried out in Mrs. Nanik's industry, she has implemented transaction ethics in accordance with sharia transaction principles. Even though the implementation is appropriate, the basis for the transactions carried out is the benefit. When transactions use the principle of benefit, which is the basis of this transaction principle, it covers all the principles of sharia transactions, so that Mrs. Nanik's home industry has carried out sharia transactions in accordance with Islamic law.